Breast-i Is an Effective and Reliable Adjunct Screening Tool for Detecting Early Tumour Related Angiogenesis of Breast Cancers in Low Resource Sub-Saharan Countries - Frank Naku Ghartey; David Watmough; Samuel Debrah; Martin Morna; Akwasi Anyanful (International Journal of Breast Cancer)
Background. What cheaper alternative breast screening procedures are available to younger women in addition to clinical breast examination (CBE) in Sub-Saharan countries? In 2009, we first described BreastLight for screening and reported high sensitivity at detecting breast cancer. Due to limitations of BreastLight, we have since 2014 been using the more technologically advanced Breast-i to screen 2204 women to find cheaper screening alternatives. Methodology. First, the participant lies down for CBE and then, in a darkened room, Breast-i was placed underneath each breast and trained personnel confirm vein pattern and look out for dark spot(s) to ascertain the presence of suspicious angiogenic lesion(s). Results. CBE detected 153 palpable breast masses and Breast-i, which detects angiogenesis, confirmed 136. However, Breast-i detected 22 more cases of which 7 had angiogenesis but were not palpable and 15 were missed by CBE due to large breast size. Overall confirmed cases were 26, with Breast-i detecting 7 cases missed by CBE. Breast-i and CBE gave sensitivities of 92.3% and 73%, respectively. Conclusion. Breast-i with its high sensitivity to angiogenesis, reliability, and affordability will be an effective adjunct detection device that can be used effectively to increase early detection in younger women, thereby increasing treatment success.